Wild-Type p53 Promotes Cancer Metabolic Switch by Inducing PUMA-Dependent Suppression of Oxidative Phosphorylation - Kim, Jinchul; Yu, Lili; Chen, Wancheng; Xu, Yanxia; Wu, Meng; Todorova, Dilyana; Tang, Qingshuang; Feng, Bingbing; Jiang, Lei; He, Jingjin; Chen, Guihua; Fu, Xuemei; et al. (Cancer cell, 2019)
The tumor suppressor p53 is somatically mutated in half of all human cancers. Paradoxically, the wild-type p53 (WTp53) is often retained in certain human cancers, such as hepatocarcinoma (HCC). We discovered a physiological and oncogenic role of WTp53 in suppressing pyruvate-driven oxidative phosphorylation by inducing PUMA. PUMA inhibits mitochondrial pyruvate uptake by disrupting the oligomerization and function of mitochondrial pyruvate carrier (MPC) through PUMA-MPC interaction, which depends on IκB kinase-mediated phosphorylation of PUMA at Ser96/106. High expression levels of PUMA are correlated with decreased mitochondrial pyruvate uptake and increased glycolysis in HCCs and poor prognosis of HCC patients. These findings are instrumental for cancer drug discovery aiming at activating WTp53 or restoring WTp53 activity to p53 mutants. [Display omitted] •WTp53-PUMA pathway drives cancer metabolic switch•PUMA suppresses mitochondrial pyruvate uptake by inactivating MPC•IKKβ-mediated phosphorylation of PUMA is important for PUMA-MPC interaction•High levels of PUMA in HCC are correlated with poor prognosis of HCC patients Hepatocellular carcinomas (HCCs) often retain the wild-type p53. Kim et al. find that p53 is important for the growth of HCC cells and that p53-regulated PUMA reduces mitochondrial pyruvate uptake and increases glycolysis in HCC, suggesting caution when designing cancer treatment strategies that activate p53.